Effect of making a match model, flashcard media, and motivation on learning outcomes - Rachyana Fahira; Daulat Saragi; Rosmala Dewi (Himpunan Pengembang Kurikulum Indonesia, 2025)
The implementation of Pancasila Education learning in elementary schools faces various challenges. This research was motivated by the low learning outcomes of students in Pancasila Education subjects, caused by a lack of learning motivation and a limited variety of teaching models. This study aimed to determine the effect of the cooperative learning model type Make A Match assisted by flashcard media on students' learning outcomes in cognitive, affective, and psychomotor domains, as well as the interaction with learning motivation. This study employed a quasi-experimental method with a 2×2 factorial design. The research subjects consisted of 42 fifth-grade students divided into experimental and control groups. Data were collected through tests and questionnaires, and analyzed using two-way ANOVA with the help of SPSS. The findings indicated that the Make A Match model, assisted by flashcard media, had a significant impact on improving students’ learning outcomes. Additionally, students with high learning motivation achieved better performance, and there was a significant interaction between the learning model and learning motivation on student outcomes. The Make A Match model with flashcards proved to be effective in fostering active and interactive learning, making it a suitable strategy for Pancasila Education. Abstrak Pelaksanaan pembelajaran Pendidikan Pancasila di sekolah dasar menghadapi berbagai tantangan. Penelitian ini dilatarbelakangi oleh rendahnya hasil belajar peserta didik dalam mata pelajaran Pendidikan Pancasila yang disebabkan oleh kurangnya motivasi belajar dan kurang variatifnya model pembelajaran yang diterapkan. Tujuan dari penelitian ini untuk mengetahui pengaruh model pembelajaran kooperatif tipe Make A Match berbantuan media flashcard terhadap hasil belajar peserta didik ditinjau dari aspek kognitif, afektif, dan psikomotorik serta interaksinya dengan motivasi belajar. Metode penelitian yang digunakan yaitu eksperimen semu dengan desain faktorial 2×2. Subjek penelitian terdiri dari 42 peserta didik kelas V yang dibagi dalam dua kelompok, yaitu kelas eksperimen dan kelas kontrol. Teknik pengumpulan data menggunakan tes dan angket, sedangkan analisis data dilakukan dengan uji ANAVA dua jalur menggunakan bantuan SPSS. Hasil penelitian menunjukkan bahwa model pembelajaran Make A Match berbantuan media flashcard berpengaruh signifikan terhadap peningkatan hasil belajar peserta didik. Temuan lain menunjukkan bahwa peserta didik dengan motivasi belajar tinggi menunjukkan hasil belajar yang lebih baik, dan terdapat interaksi signifikan antara model pembelajaran dan motivasi belajar terhadap hasil belajar. Model Make A Match berbantuan flashcard terbukti mampu menciptakan suasana belajar yang aktif dan interaktif, serta efektif diterapkan dalam pembelajaran Pendidikan Pancasila. Kata Kunci: hasil belajar; media flashcard; motivasi belajar; make a match